Pengaruh Mahkamah Bahasa Terhadap Motivasi Berbicara Bahasa Arab Santriwati Kelas XI Pesantren Ummul Mukminin ‘Aisyiyah Makassar - Berahima, Ahdiani Marfu'ah; Usman, Misnawaty; Bachtiar, Fauziah (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to determine the effect of language court implementation on the motivation to speak Arabic among female students in grade XI at the Ummul Mukminin 'Aisyiyah Islamic Boarding School in Makassar and to identify the dominant types of motivation. This study uses a mixed method approach with a mixed design involving a sample of 70 female students. Data were obtained through questionnaires and interviews and analyzed using descriptive, inferential, and qualitative statistics. The results of simple linear regression analysis showed a correlation coefficient (r) of .267 and a coefficient of determination (R²) of .071, indicating that the language court had a positive and significant effect on the motivation to speak Arabic among female students of 7.1%. The significance value of .025 < .05 confirms that the alternative hypothesis (H1) is accepted. These findings are also supported by the results of interviews with female students. The most dominant type of motivation is intrinsic motivation with an average value of 41.33. Thus, the language court is effective in increasing female students' motivation to speak Arabic, both intrinsically and extrinsically.